Electronic Finance : A New Approach to Financial Sector Development ? - Claessens, Stijn (Washington, DC: World Bank, 2013)
In recent years, electronic finance, especially online banking, and brokerage services, has reshaped the financial landscape. This paper reviews these developments, and analyzes their implications for consumers, governments, and financial service providers. First, it reviews the e-finance (r)evolution in emerging, and other markets, and projects its future growth. It then analyzes e-finance impact on the structure of, and competition in the financial services industry. After that, it assesses how e-finance, and globalization more generally, affects financial sector policies in emerging markets, including the need for changes in the approach to financial sector development. The paper then examines governments' changing role in the financial sector, and identifies opportunities that e-finance offers countries to leapfrog. Finally, the paper includes for policymakers, and others involved in financial sector reform in emerging markets, detailed information, and Web links on public policy activities related to e-finance.